Lipid Metabolism of Monkey Kidney Cells (LLC-MK-2) Infected with Chlamydia trachomatis Strain lymphogranuloma venereum - Fan, Victor S. C. (1974)
Lipid metabolism of monkey kidney (LLC-MK-2) cells and cells infected with a Chlamydia trachomatis strain lymphogranuloma venereum (LGV) was studied. The protein-to-lipid ratio of normal MK-2 cells was found to increase linearly over a 60-h period of incubation. The protein-to-lipid ratio of the infected cells was similar to that in normal cells until 36 h after infection, when a plateau in the ratio was observed. Lipid synthesis of the infected cells was found to be inhibited after 48 h of infection. Turnover of host lipids did not appear to be markedly altered by infection with LGV over a 48-h period of incubation. An anteiso branched chain of 15:0 fatty acid was found in infected cells but not in normal cells. The appearance of this fatty acid, correlated with a rise in the infectivity of LGV, suggests that synthesis of specific lipids was associated with the infection.